Differences in Carbon Acquisition Could Explain Adaptive Responses in a Baltic Sea Pico-Phytoplankton - Listmann, Luisa; Kerl, Franziska; Martens, Nele; Schaum, C-Elisa (Frontiers in Marine Science, 2021)
Pico-phytoplankton have ample scope to react to environmental change. Nevertheless, we know little about the underlying physiological mechanisms that govern how evolutionary history may affect short-term responses to environmental change. We investigated growth rates and carbon uptake related traits at 15° and 22°C and at different times during the microbial growth curve (lag phase, mid and late exponential) of eight novel strains of Ostreococcus sp. (ca. 1 μm). The strains were isolated from two distinct regions of the Baltic Sea differing in salinity and temperature as well as variability therein from North-East (Bornholm Basin) to South-West (Kiel area). Strains from Kiel area had ca. 10% higher growth rates on average and showed more variation between strains compared to strains from the Bornholm Basin. While biomass increased throughout the experiment in both temperature, CUE (carbon use efficiency, indicative of photosynthetically derived carbon available for growth) was too low to explain positive growth throughout the entire growth curve at 15°C and during the early stages at 22°C. Throughout the growth curve CUE then increased enough to sustain growth, but only at 22°C. Consequently, we then tested whether Ostreococcus use organic carbon to supplement growth when light is not a limiting factor. We show that Ostreococcus qualitatively modulate their potential to grow on organic carbon sources throughout a single growth curve. Based on the differences between CUE and a potential to grow on organic carbon, we postulate a shift in carbon acquisition between inorganic and organic sources in Ostreococcus sp. with potential implications on ecological dynamics within microbial communities.